Świeckie elementy w jednorazowych praktykach religijnych katolików miejskich. Studium socjologiczne na przykładzie badań w Kaliszu - Baniak, Józef (Polskie Towarzystwo Religioznawcze, 2012)
Józef Baniak – SECULAR ELEMENTS IN ONE OFF RELIGIOUS PRACTICES OF THE URBAN CATHOLICS. A SOCIOLOGICAL STUDY ON THE EXAMPLE OF A RESEARCH IN THE CITY OF KALISZ In this article, I show the problem of disposable desacralization of mandatory religious practices, also known as rites of passage, which play an important role in the lives of Catholics. These practices are: a baptism of newly born baby, first communion of school children, confirmation of high school students, religious wedding, religious funeral of the deceased. Desacralization of these religious practices is a slow process of elimination of sacral and religious elements of the purpose of each of these rites of passage and replacing them with secular elements. This process includes both the ideological sphere and the sphere of practical Catholics. As a result, under the impact of this process, many Catholics treat each of these religious ceremonies only as secular rites, that are, often seemingly, hardly related to religion or religious morality. The basis for the analysis of the process of transition rites desacralization are my sociological studies that I realized on separate groups of respondents in Kalisz – adults and young people. Level of desacralization of those rites is varied and depends on a variety of objective and subjective factors.